Dynamic Loan Loss Provisioning : Simulationson Effectiveness and Guide to Implementation - Wezel, Torsten (IMF Working Papers; Working Paper ;, 2012)
This simulation-based paper investigates the impact of different methods of dynamic provisioning on bank soundness and shows that this increasingly popular macroprudential tool can smooth provisioning costs over the credit cycle and lower banks' probability of default. In addition, the paper offers an in-depth guide to implementation that addresses pertinent issues related to data requirements, calibration and safeguards as well as accounting, disclosure and tax treatment. It also discusses the interaction of dynamic provisioning with other macroprudential instruments such as countercyclical capital.